Pyropia yezoensis Protein Prevents Dexamethasone-Induced Myotube Atrophy in C2C12 Myotubes - Min-Kyeong Lee; Jeong-Wook Choi; Youn Hee Choi; Taek-Jeong Nam (Marine Drugs, 2018)
Glucocorticoids (GCs), which are endocrine hormones released under stress conditions, can cause skeletal muscle atrophy. This study investigated whether Pyropia yezoensis crude protein (PYCP) inhibits synthetic GCs dexamethasone (DEX)-induced myotube atrophy associated with proteolytic systems. Mouse skeletal muscle C2C12 myotubes were treated with DEX in the presence or absence of PYCP. DEX exposure (100 μM) for 24 h significantly decreased myotube diameter and myogenin expression, which were all increased by treatment with 20 and 40 μg/mL PYCP. Additionally, PYCP significantly reduced the nuclear expression of the forkhead box transcription factors, FoxO1 and FoxO3a, and ubiquitin-proteasome pathway activation. Further mechanistic research revealed that PYCP inhibited the autophagy-lysosome pathway in DEX-induced C2C12 myotubes. These findings indicate that PYCP prevents DEX-induced myotube atrophy through the regulation of FoxO transcription factors, followed by the inhibition of the ubiquitin-proteasome and autophagy-lysosome pathways. Therefore, we suggest that inhibiting these two proteolytic processes with FoxO transcription factors is a promising strategy for preventing DEX-related myotube atrophy.